Major farm practice report in Virginia Farm 2 - Dacut, Edgardo G.; Soledad, Sim R.; Albao, Fabio T.; Gaditano, Felicisima A.; Remandaban, Eleanor T.; Bareja, Mechelin A.; Alava, Vivian Desiree V.; Peñeda, Genna C.; Declarado, Marieta A.; Tabiongan, Nona M.
This study describes the observed operations management of Virginia Farm 2 in Cebu.